Мережеві практики солідарності як прояв цифрової емпатії в метамодерному суспільстві - Анісімова, Ольга; Лукаш, Галина (Видавництво Львівської політехніки, 2025)
The article highlights the role of digital empathy – the ability to feel, understand and support others through online communication. The author analyzes online solidarity practices as a manifestation of digital empathy in the context of metamodernism. The cultural, social, and emotional functions of online solidarity practices are clarified, and their significance for the formation of a new ethics of community in the digital society is outlined.
Keywords: метамодернізм; соціальні мережі; солідарність; емпатія; цифрова емпатія; інформаційна кампанія